2015
DOI: 10.3390/ijms160921520
|View full text |Cite
|
Sign up to set email alerts
|

First Trimester Urine and Serum Metabolomics for Prediction of Preeclampsia and Gestational Hypertension: A Prospective Screening Study

Abstract: Hypertensive disorders of pregnancy, including preeclampsia, are major contributors to maternal morbidity. The goal of this study was to evaluate the potential of metabolomics to predict preeclampsia and gestational hypertension from urine and serum samples in early pregnancy, and elucidate the metabolic changes related to the diseases. Metabolic profiles were obtained by nuclear magnetic resonance spectroscopy of serum and urine samples from 599 women at medium to high risk of preeclampsia (nulliparous or pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 60 publications
2
61
0
Order By: Relevance
“…The remaining studies used urine (n = 1) (Diaz, Barros, Goodfellow, Duarte, Galhano, Pita, Almeida et al 2013), urine and serum (n = 2) (Austdal, Skråstad, Gundersen, Austgulen, Iversen, Bathen 2014; Austdal, Tangerås, Skråstad, Salvesen, Austgulen, Iversen, Bathen 2015), or breast milk (n=1) (Dangat, Upadhyay, Kilari, Sharma, Kemse, Mehendale, Lalwani et al 2016). Sixteen studies performed metabolic profiling with Mass Spectrometry (MS), while 12 used a form of nuclear magnetic resonance spectroscopy (NMR).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining studies used urine (n = 1) (Diaz, Barros, Goodfellow, Duarte, Galhano, Pita, Almeida et al 2013), urine and serum (n = 2) (Austdal, Skråstad, Gundersen, Austgulen, Iversen, Bathen 2014; Austdal, Tangerås, Skråstad, Salvesen, Austgulen, Iversen, Bathen 2015), or breast milk (n=1) (Dangat, Upadhyay, Kilari, Sharma, Kemse, Mehendale, Lalwani et al 2016). Sixteen studies performed metabolic profiling with Mass Spectrometry (MS), while 12 used a form of nuclear magnetic resonance spectroscopy (NMR).…”
Section: Resultsmentioning
confidence: 99%
“…The minimum number of metabolites for inclusion in the review was five (Sohlberg, Wikström, Olovsson, Lindgren, Axelsson, Mulic-Lutvica, Weis et al), while as many as 8000 features, as defined by their mass (mz) and retention time (rt) were included in the untargeted studies (Kelly, Croteau-Chonka, Dahlin, Mirzakhani, Wu, Wan, McGeachie et al 2016). Of the prospective studies and nested case-control studies, seven analyzed first trimester metabolites (Austdal, Tangerås, Skråstad, Salvesen, Austgulen, Iversen, Bathen 2015; Bahado-Singh, Akolekar, Mandal, Dong, Xia, Kruger, Wishart et al 2012; Bahado-Singh, Akolekar, Mandal, Dong, Xia, Kruger, Wishart et al 2013; Bahado-Singh, Syngelaki, Akolekar, Mandal, Bjondahl, Han, Dong et al 2015; Koster, Vreeken, Harms, Dane, Kuc, Schielen, Hankemeier et al 2015; Kuc, Koster, Pennings, Hankemeier, Berger, Harms, Dane et al 2014; Odibo, Goetzinger, Odibo, Cahill, Macones, Nelson, Dietzen 2011), while only three analyzed second trimester metabolites (Diaz, Barros, Goodfellow, Duarte, Galhano, Pita, Almeida et al 2013; Kenny, Broadhurst, Dunn, Brown, North, McCowan, Roberts et al 2010; Pinto, Maciel, Melo, Domingues, Galhano, Pita, Almeida et al 2014) (Figure 2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A fairly large study used both urine and serum metabolite profiles to evaluate the potential of metabolomics to predict preeclampsia and gestational hyper-tension in early pregnancy. 129 It showed that urinary metabolites provide higher sensitivity than serum metabolite profiles for the prediction of preeclampsia and gestational hypertension. The sensitivity was 51.3% (from urine) vs 15% (serum) for preeclampsia and 40% (urine) vs 33% (serum) for gestational hypertension.…”
Section: Applicationsmentioning
confidence: 99%
“…15,16,17 These agents have been most widely studied in Randomized Controlled Trials (RCTs), although systematic reviews have failed to reveal clear differences between agents. 18,19 Once blood pressure rises above a certain level; however, there is a risk of direct damage to the blood vessel wall, regardless of what caused the rise. This risk is not specific to pregnancy, as it is similar for non-pregnant people with very high blood pressure.…”
Section: Introductionmentioning
confidence: 99%